What Emotion Facial Expressions Tell Us About the Health of Others - Hareli, Shlomo; David, Or; Hess, Ursula (Frontiers in Psychology, 2020)
To avoid contagion, we need information about the health status of those whom we engage with. This is especially important when we have cause for concern that the other is indeed sick, such as is the case during the world-wide outbreak of the Corona virus in 2020. In three studies, one conducted several years before the pandemic, and two during the pandemic, we showed that facial expressions of emotions are used as signals of health status. Specifically, happy expressers are perceived as healthier than expressers showing negative emotions or neutrality (Studies 1-3), whereas anger was interpreted as a signal of ill health (Study 3). Importantly however, facial expressions affected health perception only when there was a prior reason to suspect ill health. This was the case of older expressers before and after the pandemic for whom age related stereotypes set expectations of ill health and for everyone during a wide-spread pandemic, which extends this suspicion to everyone. In Study 3, we showed that the effect of emotion expressions also generalized to the physical distance that the observer wishes to keep from the expresser. Overall, this research is the first to show a role of emotion expressions to inform health perception.